Newnes guide to radio and communications technology - Poole, Ian (Newnes, 2003)
In this brand new volume, Ian Poole begins with a fine introduction to radio, suitable for almost all readers. ... the book is an excellent way for neophytes to step into radio and learn something about it. It begins with the basics and gradually brings in more advanced concepts. We recommend it as an additon to the technical libraries of intermediate-level technical readers. It is an interesting read even for the advanced engineer. - QEX July/August 2004 Ian Poole has written a fascinating guide to the technology and applications of modern radio and communications equipment. His approach provides a useful foundation for college students and technicians seeking an update on the latest technology, but each topic is introduced from the basics, ensuring that the book is equally rewarding for managers in the communications industry, sales staff, and anyone seeking to update their knowledge of this exciting and rapidly expanding area of technology. The key areas covered by this book are: Radio principles Broadcasting, including Digital Radio Private mobile radio, (PMR) including trunking and TETRA Cellular telecommunications, including GSM and 3G Data communications, including Bluetooth and 802.11 As well as a survey of established and cutting-edge technologies the underpinning science and electronics is introduced. *Includes a survey of established and cutting-edge communication technologies *Introduces the underpinning science and electronics of the subject *Provides an emphasis on circuits and how they work.